Stress response to trace elements mixture of different embryo-larval stages of Paracentrotus lividus. (October 2022) - El Idrissi, O.; Santini, J.; Bonnin, M.; Demolliens, M.; Aiello, A.; Gobert, S.; Pasqualini, V.; Ternengo, S.
Abstract: This study investigated for the first time the oxidative biomarkers responses in all larval stages of sea urchin. The contamination effects were reproduced by using contaminated seawater to concentrations measured in the area adjacent to an old asbestos mine at factors of 5 and 10. The results suggested that the concentrations were not sufficiently high to induce a major oxidative stress. The biometric differences make this method a more sensitive approach for assessing the effects on sea urchin larvae. Measurements of specific activities of antioxidant enzymes at each stage suggested a high capacity of the larvae to respond to oxidative stress. This normal activity of the organism must be considered in future research. This work also highlighted the importance of spawners provenance in ecotoxicological studies. These data are essential to better understand the stress responses of sea urchin larvae and provide baseline information for later environmental assessment research. Highlights: The concentrations of trace elements studied do not induce a stress response. Biometric analyses are more sensitive than stress biomarkers. Paracentrotus lividus larvae have the capacity to respond to oxidative stress. Spawners origin must be taken into account in ecotoxicological studies.